The chick embryo chorioallantoic membrane as an experimental model to study lung cancer - Ribatti, Domenico (Frontiers in Oncology, 2026)
The chick embryo chorioallantoic membrane (CAM) has long been a favored system for the study of tumor growth because a chick’s immunocompetent system is not fully developed, and the conditions for rejection have not yet been established. Grafting tumors onto the CAM allows us to study the morphological aspects of the interactions of the tumors with the blood vessels of the host and to examine the identity of the vessels that supply the grafts. This article analyzes the literature data concerning the use of the CAM model to study lung cancer and the effects of anti-angiogenic molecules on the growth of this tumor due to the lack of literature data summarizing this topic.